MEDVINE - RAO, B.VENKATESWAR; RAJU, K.; MD.ASMA,; SRI, B.TEJA; SWATHI, K. (The journal of contemporary issues in business and government, 2022)
The people who are in remote areas like villages and tribal areas are facing issues in collecting the medicines. As there is no proper medical facility available in their regions. Even though they are some medical camps are conducted but only for few days the medicines are available. So, it’s difficult for the people in remote areas to get the medicine anytime they needed medicines. The main aim of the project is to help people in rural areas as they are facing difficulties in accessing healthcare facilities. It is designed by different electric components to dispense different medicines using coins. It can be placed at government medical hospitals or urban primary health cares. And it also includes symbols to make it easy for rural people to understand the description of the project.